Prognostic biomarkers in oral squamous cell carcinoma: A systematic review. (September 2017) - Rivera, César; Oliveira, Ana Karina; Costa, Rute Alves Pereira; De Rossi, Tatiane; Paes Leme, Adriana Franco
Highlights: Systematic review performed to identify published prognostic OSCC biomarkers. Evaluation of oral cancer biomarkers related to common clinical endpoints. Forty-one potential biomarkers are awaiting for validation in cohort-based studies. Abstract: Over the years, several tumor biomarkers have been suggested to foresee the prognosis oral squamous cell carcinoma (OSCC) patients. Here, we present a systematic review to identify, evaluate and summarize the evidence for OSCC reported markers. Eligible studies were identified through a literature search of MEDLINE/PubMed until January 2016. We included primary articles reporting overall survival, disease-free survival and cause-specific survival as outcomes. Our findings were analysed using REporting recommendations for tumor MARKer prognostic studies (REMARK), QuickGo tool and SciCurve trends. We found 41 biomarkers, mostly proteins evaluated by immunohistochemistry. The selected studies are of good quality, although, any study referred to a sample size determination. Considering the lack of follow-up studies, the molecules are still potential biomarkers. Further research is required to validate these biomarkers in well-designed clinical cohort-based studies.